Evaluation of the Football Development Program in Deli Serdang Regency, North Sumatra (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
Abstract___________________________________________________________________This study aims to analyze programs, namely antecedents, transactions, outcomes of the Deli Serdang PSDS club football coaching program. This study uses the Countenance Evaluation Model (Stake) in terms of the antecedents, transactions and outcomes stages, which means getting accurate and objective information and comparing what has been achieved from the achievement of the development program. Data collection techniques in this study were observation, interviews, and documentation that came from coaches, administrators, athletes, and the community. The qualitative analysis technique is based on 4 components, namely: data collection, data reduction, data presentation, and conclusion drawing. The results are the Antecedent coaching program that is clear in improving the achievement of PSDS athletes, the PSDS football athlete development program has been running well, Transaction has not been going well, Outcome, the PSDS football achievement coaching program carried out in Deli Serdang Regency from the results of the trophy has experienced drop. The conclusion is that Antecedents at the PSDS club have management, human resources, facilities and infrastructure, funding, a clear and targeted training program, Transaction in the PSDS football athlete development program which is declared good but still lacks in its implementation, Outcomes in this case the results are not good, For the athleteâ€™s own achievement, it is less stable in obtaining trophies every year and does not routinely take part in League 3 competitions every year so that their achievements decrease. Â© 2020 Semarang State University